Democratization of Englishes: synchronic and diachronic approaches. (May 2020) - Hiltunen, Turo; Loureiro-Porto, Lucía
Abstract: The term democratization has been used in recent linguistic research to describe how specific linguistic changes can be linked to changes in sociocultural norms. This broad definition, however, does not fully capture the essence of this phenomenon or explain how it differs from other processes of language change. Other key issues in this area of research include what the cause-effect relationship is between linguistic change and social change, and how empirical corpus linguistic studies can contribute to current knowledge. In this opening contribution to the special issue New perspectives on democratization: Evidence from English(es), we address some of these key issues by reviewing previous synchronic and diachronic work studies on democratization in different varieties of English, and introduce new studies that take evidence from different linguistic corpora. By placing the linguistic changes into their specific socio-historical contexts, these studies yield interesting results, showing that variationist linguistic methodology may significantly contribute to disentangling the complex relationship between language change and social and societal changes.